Effect Of Ascaris Lumbricoides On Some Hematological Parameters And The Concentration Levels Of Interleukin-10 And Interleukin-22 - AL-Salami, Eman Hasani; Sarhan, Nadia Habeeb; Al-Roubaey, Dina A. A. (Medical Science Journal for Advance Research, 2023)
Background: The parasite Ascaris lumbricoides modifies the host’s immunological response. This study aims to determine the interleukin-10 (IL-10) and interleukin-22 (IL-22) serum levels in specific patients and their associations with the severity of infection. The present study also requires to study a few blood markers in Ascaris lumbricoides-infected patients.Patients were referred to the laboratory for testing from Al Sader General Hospital in AL-Najaf Province, Al Furat General Hospital, AL-Zahra maternity and pediatrics, and AL-Hakeem Hospital. Samples Collected 32 samples were taken from patients and 20 healthy individuals who attended clinics at the AL-Sadder Teaching Hospital and AL-Hakeem Hospital in the province of AL-Najaf between July 2021 and June 2022. Male and female patients between the ages of 10 and 50 had their stool samples taken and put in clean, wide-mouth specimen bottles. The same patients’ veins were also punctured to get five milliliters of blood, four milliliters of which were then deposited in specimen tubes. After 30 minutes at room temperature, stool samples were examined using the Formol-ether concentration and Kato-Katz thick smear procedures. According to the findings, ascariasis patients had significantly higher serum levels of interlukin-10 and interlukin-22 than the healthy group (P0.05). The findings showed that the iron level concentration in ascariasis patients decreased significantly (P0.05), and that the Hb, PCV, and RBC count also decreased significantly (P0.05).